How much justice is denied? An estimate of unsubmitted sexual assault kits in the United States. (March 2021) - Strom, Kevin; Scott, Thomas; Feeney, Hannah; Young, Amanda; Couzens, Lance; Berzofsky, Marcus
Abstract: Purpose: Prior national, state, and local investigations of law enforcement agencies have revealed large stockpiles of sexual assault kits (SAKs) that were not submitted to a laboratory for forensic testing. The failure to submit these SAKs has resulted in incomplete investigations for sexual assault victims and a lack of accountability for sexual assault offenders. To direct national policy aimed at testing these kits and reducing future stockpiles, it is essential to realize the magnitude of the problem. Methods: This study uses information on known unsubmitted SAK counts from 911 counties in 15 states and a multitude of county-level covariates to estimate the national number of unsubmitted SAKs during the period 2014–2018. Results: Based on 95% confidence intervals, there were an estimated 300, 000 to 400, 000 unsubmitted SAKs in the United States during this period. A county's population was the strongest predictor of whether the county had an unsubmitted SAK count, while county sociodemographic factors and state legislative actions were the strongest predictors of the size of county unsubmitted SAK counts. Conclusions: To improve future estimates, LEAs should account for SAKs throughout the investigative and laboratory submission stages and states should conduct annual high-quality audits that leverage tracking processes. Highlights: Vast amounts of sexual assault kits are never submitted for forensic testing by law enforcement agencies. Imputation and estimation model found between 300, 000–400, 000 unsubmitted sexual assault kits between 2014 and 18. County sociodemographic characteristics, crime levels, and state legislation predict county unsubmitted sexual assault kit counts. Lack of state data is a major issue for informed decisions to reduce the rape kit backlog